The testing of materials of construction a text-book for the engineering laboratory and a collection of the results of experiment - Unwin, William Cawthorne, 1838-1933 (Longmans, Green, and Co., 1899)
This treatise on the strength of the materials used in construction considers those materials in connection with the instruments and methods by which the mechanical properties of materials are investigated experimentally.